Espelho da Cruz (cód. alc. 221): edição e estudo - Marcos Alexandre dos Santos (2022)
This dissertation contains a paleographic edition of the medieval manuscript in Portuguese Mirror of the Cross of the Alc. cod. 221 and a study of the interventions in this testimony in comparison to the Alc. cod. 89, also a testimony in Portuguese of the same text, both kept in the National Library of Portugal, in Lisbon. The work is structured in seven sections, with the first one containing comments on the chosen theme and the approach on which it was produced, reaffirming its importance in the fields of Linguistics and Textual Criticism. The intended objectives are also discussed and the results achieved are briefly presented. In section 2 aspects related to the object of study are described, such as the biography of the author of the text, the Italian Domenico Cavalca, the main information about the copy/translation (authorship, structure and content) and the codicological and paleographic descriptions, including the alphabet of graphemes used in the testimony. In section 4, a review of the Romance and Portuguese traditions of the text is made, presenting how this discussion currently stands. The fifth section contains the edition norms used and the paleographic edition. Next, in section 6 there is the study of the interventions carried out by the actors involved in the production of the copy in Portuguese. To develop it, the methodology used went through the phases of data collection (interventions in the testimony), its classification (in the relevant linguistic categories) and the analysis (quantitative and qualitative), leaving room for a meticulous appreciation of the most relevant data, taking into account facts previously described by Cambraia and Santos (2019) and other authors about the presence of multilingualism in the Al.c cod. 221, especially traces of Spanish and Catalan. Finally, in the last section, the most relevant features of the work are recalled and future developments are envisaged.